The Role of Universitas Terbuka in Increasing the Gross Enrolment Ratio (GER) of Higher Education in Indonesia: A Comparative Study of Open Universities in Malaysia, Singapore, and Thailand - Abdul Rahman Rahim; Effendi Effendi; Jalil Jalil; Safri Safri; Wahyuddin Wahyuddin (Danadyaksa: Post Modern Economy Journal, 2026)
This study examines the role of Universitas Terbuka (UT) in increasing the Gross Enrolment Ratio (GER) of higher education in Indonesia, identifies supporting and inhibiting factors, and compares the strategies of open universities in Malaysia, Singapore, and Thailand to formulate recommendations for UT Indonesia. The research uses a descriptive qualitative approach, with primary data collected through observations and in-depth interviews with UT administrators, lecturers, and stakeholders, complemented by comparative analysis of international practices. Data were analysed using qualitative techniques, including data reduction, data display, and conclusion drawing. The results indicate that UT has contributed significantly to the national GER, with an average contribution of 16.12% and an increase to 19.19% in 2024. This contribution is supported by UT’s status as a public university, strong accreditation, government policy support, and flexible learning systems that expand access for remote communities and working adults. Comparative findings show that open universities in the selected countries emphasize inclusive education, digital learning, policy integration, and international collaboration. Based on these findings, UT Indonesia needs to strengthen digital transformation, expand blended learning, and enhance internationalization to improve competitiveness and support national human resource development.